Suppliers’ perspective on case company’s position as a customer : an empirical evidence on factors influencing the buyer’s attractiveness - Mattila, Lauri (My University, 2022)
Most of the resources consumed by the manufacturing industry are sourced from external suppliers and the buying company is not always a stronger party in the market. In an ever-changing market condition, the relative strengths between the buying company and suppliers may alternate significantly. In the current situation, a global pandemic, disruptions in steel production due to increased electricity prices, and a shortage of semiconductors have pushed manufacturing companies into a difficult situation. Companies that suppliers perceive as the most attractive customers can mobilize the best external resources. The attractiveness of the customer may eventually lead to a situation where the buyer company becomes the preferred customer. This study seeks to define the status of the case company as a customer in the eyes of suppliers, as well as to identify the factors affecting its customer attractiveness. The case company is aware that the high-quality and competent supplier network is a significant competitive advantage for them. However, there was not a very precise picture of the company’s own position as a customer, and it was considered an important topic during the sourcing strategy-making process. The purpose of the study was also to identify factors that increase and decrease the case company’s customer attractiveness. In prior research, customer attractiveness has been mainly addressed from the perspective of the buying company, and the focus has been on strategic supplier relationships. In this study, the customer attractiveness is approached from the suppliers’ perspective and the study considers not only strategic suppliers but also routine, volume, and bottleneck suppliers. Empirical research is based on qualitative data collected through 13 semi-structured interviews. The interviewees were representatives of the suppliers of the case company, and they have worked at the customer interface for several years. The themes and questions of the interview were based on prior literature, research questions, and discussions in the case company. The study found that the case company is perceived as a very important customer who has also partially managed to achieve preferred customer status. This is reflected in tight collaboration with the supplier, prioritization, and the suppliers’ desire to invest in the customer relationship and its development. The most contributing factors to customer attractiveness were the customer's growth and development potential and the financial profitability of the business relationship. Inversely, cold and distant relationships, inaccuracy of order forecasts received from the customer, and the lack of common system interfaces were highlighted as factors that would reduce the case company’s customer attractiveness. Based on the findings, five recommendations for action are proposed for the case company, which are presented at the end of the work.

Suurin osa valmistavan teollisuuden käyttämistä resursseista hankitaan yrityksen ulkopuolisilta toimittajilta eikä ostava yritys ole aina vahvempi osapuoli markkinoilla. Alati muuttuvissa markkinatilanteissa ostavan yrityksen ja toimittajien väliset voimasuhteet saattavat muuttua hyvinkin merkittävästi. Nykyisessä maailmantilanteessa globaali pandemia, kasvaneesta sähkön hinnasta johtuvat häiriöt terästuotannossa sekä pula puolijohteista ovat ajaneet valmistavan teollisuuden yritykset ahtaalle. Ostajayritykset, jotka toimittajat kokevat houkuttelevimpina asiakkaina, saavat mobilisoitua parhaat ulkoiset resurssit. Asiakkaan houkuttelevuus saattaa lopulta johtaa tilanteeseen, jossa ostajayrityksestä tulee ensisijainen asiakas. Tällöin asiakkaan tilauksia priorisoidaan, se saa suuren osan toimittajan huomiosta ja mahdollisia myönnytyksiä hinnoissa. Tämä tutkimus pyrkii selvittämään kohdeyrityksen aseman asiakkaana toimittajien silmin sekä sen asiakashoukuttelevuuteen vaikuttavat tekijät. Toimeksiantajayrityksessä tiedostetaan, että laadukas ja osaava toimittajaverkosto on heille suuri kilpailuvaltti. Yrityksen omasta asemasta asiakkaana ei kuitenkaan ole kovin tarkkaa käsitystä, ja sen selvittäminen koettiin tärkeäksi aiheeksi hankintaorganisaation strategiapalaverien yhteydessä. Tutkimuksen tarkoituksena oli myös selvittää tekijät, jotka lisäävät ja vähentävät kohdeyrityksen asiakashoukuttelevuutta. Asiakashoukuttelevuutta on aikaisemmissa tutkimuksissa käsitelty lähinnä ostavan yrityksen näkökulmasta, ja pääpaino niissä on ollut strategisissa toimittajasuhteissa. Tässä tutkimuksessa ostavan yrityksen houkuttelevuutta lähestytään toimittajien näkökulmasta ja tutkimuksessa huomioidaan strategisten toimittajien lisäksi myös rutiini-, volyymi- ja pullonkaulatoimittajat. Empiirinen tutkimus perustuu kvalitatiiviseen dataan, joka kerättiin 13 puolistrukturoidun haastattelun avulla. Haastateltavat olivat kohdeyrityksen toimittajien edustajia, jotka ovat työskennelleet asiakasrajapinnassa useita vuosia. Haastattelun teemat ja kysymykset laadittiin aiemman kirjallisuuden, tutkimuskysymysten ja kohdeyrityksessä käytyjen keskustelujen pohjalta. Tutkimuksessa havaittiin, että kohdeyritys nähdään erittäin tärkeänä asiakkaana, joka on myös osittain onnistunut saavuttamaan ensisijaisen asiakkaan aseman. Tämä näkyy hyvin tiiviinä yhteistyönä toimittajan kanssa, priorisointina, sekä toimittajan haluna investoida asiakassuhteeseen ja sen kehittämiseen. Asiakashoukuttelevuutta lisäävissä tekijöissä korostui asiakkaan kasvu- ja kehityspotentiaali sekä liiketoimintasuhteen taloudellinen kannattavuus. Vastaavasti kylmä ja etäinen suhde asiakkaan kanssa, asiakkaalta saatujen tilausennusteiden epätarkkuus ja yhteisten järjestelmärajapintojen puute korostuivat asiakashoukuttelevuutta vähentävissä tekijöissä. Havaintojen perusteella kohdeyritykselle on laadittu viisi toimenpidesuositusta, jotka esitellään työn lopussa.
Keywords: hankinta; resurssit; tavarantoimittajat; teknologiayritykset; yritysstrategiat; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Systems Analytics